The Influence of Islamic Identity Politics on Thought Patterns and Social Life in the Perception of Gen Z - Shobirin, Taufik Ismail; Rahman, Ahmad Arizzal; Zakaria, Muhammad Husni; Faqihuddin, Achmad; Orwela, Citra (Institut Agama Islam Negeri Kediri, 2024)
This study aims to explore Gen Z's perceptions of Islamic identity politics in Indonesia and its impact on their mindset and social life. This study uses a quantitative approach with a survey method of 62 respondents, the majority of whom are students. Data were collected through a Likert-based questionnaire designed to measure respondents' understanding and views on identity politics. The results showed that 43.5% of respondents considered Islamic identity politics to have the potential to divide society, while 51.6% of respondents considered the use of religious symbols in political campaigns to be quite effective. In addition, 77.5% of respondents acknowledged the major role of social media in shaping their views. Data analysis was conducted using descriptive and inferential statistical methods, which showed a significant relationship between identity politics and Generation Z's mindset and social life. This is manifested by the important role of a more inclusive approach in religious-based political policies in Indonesia. This finding is able to reflect how the younger generation is increasingly aware of complex social and political issues and shows their tendency to assess religious issues more rationally and openly. Therefore, this study provides an important contribution in understanding the dynamics of identity politics from the perspective of the younger generation who will be the main actors in the future of Indonesian democracy.